Data Science Analysis on UIN Raden Mas Said’s Media Accounts - Tigus Juni Betri; Haya Nur Fadhilah; Galih Fajar Nugroho (International Journal of Science and Applied Science: Conference Series, 2024)
Abstract: Social Media is an important part of human life in this era. Instagram is not only effective for communication but also effective for promotional activities. Ideally, every promotional content is created based on the target market. The Instagram account @uin.surakarta provides information about the Raden Mas Said Surakarta State Islamic University. Social media analysis with data science innovation allows institutions or account owners to easily identify audiences and understand their needs regarding the content displayed. This aims to enable social media account owners to create effective marketing strategies, present more targeted content products, and improve audience relationships. This study aims to analyze and provide data science innovations to support institutional promotional activities. The research method used is descriptive qualitative. The study results show that these accounts can be more useful with the right data approach